2002
DOI: 10.1080/1025389021000010503
|View full text |Cite
|
Sign up to set email alerts
|

Can the Behaviour Abnormalities Induced by Gestational Stress in Rats be Prevented or Reversed?

Abstract: Gestational stress increases circulating maternal hormones that produce changes in behaviour and impair the feedback regulation of the hypothalamic pituitary adrenal axis of the offspring. Prenatally-stressed (PS) rats also release more corticotropin-releasing hormone (CRH) in the limbic system in response to stimulation than controls. This contributes to their exaggerated fear of intimidating situations and depressive-like behaviour. By using different treatments given to the pregnant mother, to neonatal or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 99 publications
1
33
0
4
Order By: Relevance
“…Moreover, in studies of both humans and animals, many different types of prenatal stressors were found to have significant effects on postnatal behavior. Weinstock (2002), for example, noted that procedures used to induce stress in pregnant rats have included saline injections, physical restraint, exposure to loud noises, foot-shocks, overcrowding, and immersion in cold water. The effects of exposure to prenatal stress on postnatal behavior have also been produced by exposing pregnant monkeys and rodents to stress hormones such as glucocorticoids (GCs) (Matthews, 2000;Scheepens et al, 2003).…”
Section: Different Types Of Prenatal Stressors Can Affect Postnatal Dmentioning
confidence: 99%
“…Moreover, in studies of both humans and animals, many different types of prenatal stressors were found to have significant effects on postnatal behavior. Weinstock (2002), for example, noted that procedures used to induce stress in pregnant rats have included saline injections, physical restraint, exposure to loud noises, foot-shocks, overcrowding, and immersion in cold water. The effects of exposure to prenatal stress on postnatal behavior have also been produced by exposing pregnant monkeys and rodents to stress hormones such as glucocorticoids (GCs) (Matthews, 2000;Scheepens et al, 2003).…”
Section: Different Types Of Prenatal Stressors Can Affect Postnatal Dmentioning
confidence: 99%
“…Diversos trabalhos têm mostrado que os efeitos do estresse pré-natal sobre o funcionamento do eixo HPA são mais pronunciados após a exposição dos animais a um outro estresse na idade adulta (WEINSTOCK, 1997(WEINSTOCK, , 2001(WEINSTOCK, , 2002. Assim, como no presente experimento os níveis de estimulação ambiental eram pequenos ou mínimos no campo aberto, não induziram, provavelmente, qualquer alteração na atividade do eixo HPA, isto é`não representaram um estresse adicional.…”
Section: Resultsunclassified
“…Alterações do funcionamento do eixo HPA nos animais estressados já foram descritas por vários autores (TAKAHASHI; KALIN, 1991;TAKAHASHI et al, 1988;WEINSTOCK, 1997WEINSTOCK, , 2002WEINSTOCK, , 2005WEINSTOCK et al, 1992 …”
Section: Resultsunclassified
See 2 more Smart Citations